Hardness behaviour of carbon nanotube-aluminium nano-composite using nanoindentation technique - Abdullahi, Umma; Maleque, Md. Abdul; Ali, Mohammad Yeakub (Elsevier Ltd., 2020)
The aim of the current paper is to study the hardness behaviour of carbon nanotube reinforced aluminium (CNT-Al) nano composite material under nanoindentation and Vickers micro hardness techniques. The four different types of nano-composites with 1, 1.5, 2.0 and 2.5 wt% CNT indented by diamond Berkovich indenter in sub microns. The Vickers micro hardness test was performed using a Wilson Wolpert Vickers micro hardness tester. The results showed that the value of hardness increases with the increasing of CNT percentage in Al matrix up to 2 wt%. The highest hardness was obtained from 1.5 wt% CNT-Al nano-composite with the value of 1.90 GPa. From the CNT-Al load-displacement curve a good bonding property was observed between the reinforcement and the matrix material due to the same trend followed with other strong materials such as steel and silicon. However, there is a significant enhancement in the Vickers micro hardness of the 1.5 wt% CNT-Al nano-composite compared to other CNT reinforcement nano-composites. The highest hardness with the value of 102 VH was obtained from 1.5 wt% CNT-Al nano-composite which is three times higher than pure Al.